KETERGANTUNGAN SEMAI JOHAR (Cassia siamea LAMK) TERHADAP FUNGI MIKORIZA ARBUSKULA PADA MEDIA TAILING TAMBANG EMAS - Setyaningsih, Luluk (Universitas Pattimura, 2023)
Tailings are the wastes resulting from mining activities in the amalgamation of mine ore from the ground, with extreme characteristics such as a sand-dominated texture, high Pb heavy metal content, very low availability of carbon and macro nutrients. Consequently, the plants may not able to grow well in the tailings. The application of Arbuscular Mycorrhyza Fungi (AMF) is expected to increase the ability of forest plant seedlings to grow and develop in tailings media. The research was carried out in a greenhouse using johar (Cassia siamea Lamk) seedlings which were inoculated with AMF inoculum: Glomus manihotis, Glomus etunicatum, and mix inoculan (mycofer), and planted in tailings media collected from Pongkor gold mine for 8 weeks. Johar seedlings were able to grow in tailings media and AMF colonization to the seedlings was observed. The compatibility of multi-species inoculum, mycofer, is higher than single AMF inoculum. The height, diameter and biomass growth of johar seedlings in tailings media significantly (p<0.05) increased with AMF inoculation. Johar seedlings have a high dependence on AMF, on tailings media, undicated by value of MIE > 50%, suggesting that the AMF application to johar is very necessary for revegetation activities in tailings media.